Modelling of P-waves velocity function from the PKiKP and PKIKP phases - Ramírez-Nicolás, María (Física de la Tierra, 2012)
The structure of the Earth is characterized by a number of regions which have different physical properties. For their study one uses models such PREM or IASPEI91. These models describe the internal structure of the Earth providing us the theoretical values of the velocity of the waves that pass through each of these regions. In this paper we focus on the waves that cross the inner core (PKIKP), and the reflected waves on the surface of the inner core (PKiKP). The aim of this study is to identify the PKiKP and PKIKP phases in a seismogram and compare them with the theoretical values obtained from the models. Another objective of this work is to propose an expression for the propagation velocity of seismic waves at the discontinuity between the outer and inner core from the minimization of waste of time (time difference between the arrival of the wave PKIKP and PKiKP). For this study we have selected two earthquakes, one occurred in Colombia, 04/26/1999 (Mw = 5.9) and the other in Peru-Ecuador 16/11/2007 (Mw = 6.8). We have analyzed only the seismograms from stations with epicentral distances between 130º and 140º, because of the interference phenomena between the PKIKP and the PKiKP for epicentral distances less than 130º.
Keywords: Inner core; IASPEI91; PREM; PKIKP; PKiKP.